Tumpeng Sêga Punar: Eksplorasi Simbolik Kuliner dalam Perayaan Tradisional Jawa terhadap Kesadaran Gizi Seimbang Masyarakat - Salsabila, Nazwa Nisella; Nikma, Arsyatul; Alberta, Rena Erlya; Syahr, Aisyah Nuril Alfi; Ulayya, Falihah Mishbah; Agustin, Pradita Triya (Universitas Negeri Malang, 2024)
Tumpeng sêga punar is one of the symbols of Javanese culture that is rich in meaning and philosophy. This research aims to explore the symbolic values of tumpeng sêga punar in the eyes of Javanese people, to know the perspective of public health experts on the existence of tumpeng sêga punar, and to know its nutritional value. The research method used was a qualitative approach with descriptive method. Data were collected through in-depth interviews with six Javanese ethnic women with different regional backgrounds who have an age range of 40–60 years and one public health expert who focuses on nutrition. The process of identifying the nutrition of tumpeng sêga punar itself was carried out using NutriSurvey software. Data analysis techniques used are data reduction, coding data, data presentation, and conclusion. The results showed that tumpeng sêga punar became one of the traditional culinary symbols in Java with a cone shape that depicts mountains, stages of life, and a peak of gratitude. While the yellow color describes glory, gold, and endless sustenance. Similarly, the side dishes also have their own meaning. In addition, tumpeng sêga punar also plays an important role in efforts to achieve balanced nutrition in the community and can be used as an effective medium for nutrition counseling or education. Thus, tumpeng becomes a dish philosophy that is rich in meaning and affects the nutritional awareness of the community at large.